Iowa Birdline update, October 17, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for October 17, 1994. Highlights of the update include the return of Bald Eagles to the state as well as the sightings of an Ibis and a Red-necked Grebe. Also of note was the observation of ten shorebird species at the Runnells Game Area, including American Avocet, Dunlin, and Western Sandpiper. Also included are typewritten notes for the next week's update with sightings of a first winter Laughing Gull, a Sandhill Crane, and a late Philadelphia Vireo. Epson - sheet feed/flatbed